Capacity Building for the Planning, Assessment and Systematic Observations of Forests With Special Reference to Tropical Countries - Singh, Karan Deo.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book is intended to support the forestry institutions in the tropical countries in the planning, assessment and systematic observation of forests required to fulfill their obligations as laid in international conventions such as the CBD and UNFCCC. Following the Rio Conference, a number of countries, donors and international organizations have implemented capacity-building projects with varying degrees of success. One main reason for the varying success rates seems to lie in the design of technical assistance programs, which have been formulated on the traditional lines of mainly generating forest resources information or transferring technology; whereas Agenda 21 requires fundamental changes in countries$1 (Binstitutions and approaches to planning and implementing the conservation and sustainable development of forests through a process of continuing research and analysis. The book is intended to serve the basic needs of national planning strategies and international and donor support.s
The Growing Mandate OF Forest Inventories -- Forest Inventory Problem Formulation -- Organizing the Existing Information -- Technology Transfer and Applications -- Building Capacity for Planning and Forest Assessments -- Statistical Planning -- Special Studies -- Data Collection -- Data Processing -- Report Writing.
Keywords: Geography; Forests and forestry; Sustainable development; Earth Sciences; Environmental Science and Engineering; Forestry; Sustainable Development